High-temperature safety negative electrode current collector and application thereof in preparation of lithium battery

CN122677457BActive Publication Date: 2026-10-27SHENZHEN EPT BATTERY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611190178.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

然而,聚偏氟乙烯的玻璃化转变温度较低,在60摄氏度高温长期存储过程中,粘结剂逐渐软化,涂层与正极铝箔之间的界面结合力明显衰减,导致活性物质层剥离、容量衰减,严重时甚至引发极片卷曲

Benefits of technology

1.本申请通过γ-氨丙基三乙氧基硅烷对甲基乙烯基聚硅氮烷进行改性,在聚硅氮烷主链上引入氨丙基侧链。该氨丙基侧链能够与正极铝箔表面天然氧化铝层上的羟基形成氢键和配位键,大幅提高了底涂层与正极铝箔之间的界面结合力。在60℃高温长期存储过程中,这种强界面结合有效抑制了因粘结剂软化导致的活性物质层剥离和极片卷曲,使底涂层在高温环境下仍保持稳定的附着状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122677457B_ABST
    Figure CN122677457B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium batteries, and specifically discloses a high-temperature safety bottom-coated positive electrode current collector and application thereof in preparation of lithium batteries, which comprises a positive electrode aluminum foil and a bottom coating layer arranged on the surface of the positive electrode aluminum foil, the bottom coating layer is obtained by coating and curing of a bottom coating slurry, and the bottom coating slurry comprises aminopropylsilazane, silanized boehmite and hydroxylated boron nitride nanosheet; the aminopropylsilazane is prepared by condensation reaction of methylvinyl polysilazane and gamma-aminopropyl triethoxysilane; the silanized boehmite is prepared by reaction of boehmite and gamma-aminopropyl triethoxysilane; and the hydroxylated boron nitride nanosheet is prepared by hydroxyl treatment of hexagonal boron nitride powder. The surface group matching and in-plane orientation intercalation design of the aminopropylsilazane, the silanized boehmite and the hydroxylated boron nitride nanosheet make the bottom-coated positive electrode current collector have excellent interface bonding force, realize the unity of in-plane rapid heat dissipation and high-temperature structural locking, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery technology, specifically relating to a high-temperature safety bottom-coated positive electrode current collector and its application in the preparation of lithium batteries. Background Technology

[0002] In lithium-ion batteries, the positive electrode current collector is typically made of aluminum foil. A base coating layer is often placed between the foil's surface and the positive electrode active material layer. This base coating layer serves multiple functions in the battery structure, including interfacial bonding, physical barrier, and thermal dispersion. On one hand, the base coating layer needs to adhere firmly to the surface of the positive electrode aluminum foil, providing a stable supporting interface for the subsequently coated active material layer. On the other hand, when the battery is subjected to mechanical abuse such as punctures or compression, or thermal abuse such as high-temperature storage, it needs to prevent direct contact between the positive electrode aluminum foil and the negative electrode, which could lead to an internal short circuit. Simultaneously, it needs to control localized heat accumulation and prevent thermal runaway caused by the thermal shrinkage of the separator.

[0003] Currently, the base coatings widely used in industry mostly use polyvinylidene fluoride (PVDF) or acrylic polymers as binders, combined with ceramic fillers such as boehmite for coating and drying. These organic binders have good film-forming properties and flexibility at room temperature, and can form a certain degree of physical adsorption with the aluminum foil surface. The boehmite layer can play a basic physical barrier role in the coating. However, PVDF has a low glass transition temperature. During long-term storage at 60 degrees Celsius, the binder gradually softens, and the interfacial bonding force between the coating and the positive electrode aluminum foil is significantly weakened, leading to peeling of the active material layer, capacity decay, and in severe cases, even electrode curling. In addition, boehmite itself has poor thermal conductivity, and the overall thermal conductivity of the coating is usually less than 0.5 W / m Kelvin. When needle penetration causes a rapid generation of local Joule heat, the heat is difficult to dissipate quickly and can only be conducted to the separator along the coating thickness direction. Once the local temperature of the separator exceeds the thermal shrinkage temperature, the battery will experience thermal runaway.

[0004] To improve high-temperature resistance, some researchers have attempted to replace organic binder systems with pure inorganic ceramic coatings, such as constructing all-inorganic undercoats based on alumina or boehmite. These coatings do not soften or decompose at high temperatures and exhibit good structural stability, but they are brittle at room temperature and have poor interfacial bonding with the positive electrode aluminum foil and active material layer. During battery charge-discharge cycles, they are prone to pulverizing and detaching due to volume expansion and contraction, which actually reduces long-term reliability.

[0005] Some technical approaches involve simply mixing thermally conductive fillers such as boron nitride and alumina into an organic matrix in an attempt to improve the heat dissipation capacity of the coating. However, boron nitride nanosheets have poor dispersibility in polar solvents, are prone to agglomeration and sedimentation, and randomly distributed fillers are unlikely to form continuous and effective thermal conduction channels, resulting in limited improvement in in-plane thermal conductivity. When boehmite and boron nitride are simply blended, the two fillers lack interfacial matching and cannot form a synergistic intercalation orientation structure. The barrier function and the thermal conduction function are independent, and it is impossible to achieve both rapid heat dissipation in the in-plane direction and thermal insulation in the thickness direction simultaneously.

[0006] Polysilazane, as a ceramic precursor, can be transformed into silicon-carbon-nitrogen-oxygen ceramics at high temperatures, exhibiting excellent heat resistance. However, polysilazane has relatively high rigidity at room temperature, resulting in insufficient wettability and adhesion to the surface of the positive electrode aluminum foil. When directly coated, the interfacial bonding is weak, and its ceramicization transition temperature typically requires above 400 degrees Celsius. Within the localized temperature rise range of 150 to 200 degrees Celsius caused by needle penetration, it cannot quickly respond to form a rigid skeleton, making it difficult to lock the coating structure in time during the initial stage of thermal abuse and prevent collapse.

[0007] In summary, existing bottom-coated cathode current collector technologies cannot simultaneously ensure interfacial stability during high-temperature storage and structural rigidity under thermal abuse, while inorganic ceramic coatings struggle to meet the requirements for room-temperature flexibility and interfacial adhesion. Furthermore, the introduction of thermally conductive fillers is mostly limited to simple blending, failing to form a synergistic microstructure with the matrix resin and barrier framework. Therefore, there is a need to design a high-temperature safe bottom-coated cathode current collector and its application in lithium-ion battery fabrication. Summary of the Invention

[0008] To overcome the shortcomings of existing technologies, a high-temperature safe bottom-coated positive electrode current collector and its application in the preparation of lithium batteries are provided.

[0009] To achieve the above objectives, the present invention provides the following technical solution: A high-temperature safety-graded positive electrode current collector includes a positive electrode aluminum foil and a base coating disposed on its surface. The base coating is obtained by coating and curing a base coating slurry, which includes aminopropylsilazane, silanized boehmite, and hydroxylated boron nitride nanosheets. Aminopropylsilazane is prepared by the condensation reaction of methylvinylpolysilazane and γ-aminopropyltriethoxysilane; Silanized boehmite is prepared by reacting boehmite with γ-aminopropyltriethoxysilane; Hydroxylated boron nitride nanosheets are prepared by hydroxylation of hexagonal boron nitride powder.

[0010] The preparation method of the primer slurry includes the following steps: Dissolve 100 parts by weight of aminopropylsilazane in N-methylpyrrolidone to prepare an N-methylpyrrolidone solution of aminopropylsilazane with a solid content of 25-35%. 150-300 parts by weight of silanized boehmite and 50-150 parts by weight of hydroxylated boron nitride nanosheets were added to N-methylpyrrolidone and ball-milled to obtain a pre-dispersed slurry; The pre-dispersed slurry is added to an N-methylpyrrolidone solution of aminopropylsilazane, and 0.5-1.5 parts by weight of di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone is added. N-methylpyrrolidone is then added to adjust the total solid content to 15-25%. The mixture is stirred at low speed for 30 minutes to obtain the primer slurry.

[0011] The specific parameters of the ball mill are as follows: the ball milling medium is zirconia balls, the ball-to-material mass ratio is (3-5):1, the ball milling speed is 200-400 revolutions per minute, and the ball milling time is 2-3 hours.

[0012] The coating and curing process specifically includes the following steps: applying a primer slurry to the surface of the corona-roughened positive electrode aluminum foil using a slot coating method, with a wet film thickness of 10-15 micrometers, a coating speed of 10-20 meters per minute, and a coating gap of 1.2-1.5 times the aforementioned wet film thickness; then pre-drying at 80°C for 20 minutes, followed by curing in an oven at 100-110°C for 60 minutes, with the curing atmosphere being air and a relative humidity of 40-60%, resulting in a primer coating with a dry thickness of 1.5-3 micrometers.

[0013] The preparation method of the aminopropylsilazane includes the following steps: methyl vinyl polysilazane and γ-aminopropyltriethoxysilane are added to anhydrous toluene, dibutyltin dilaurate is added, and the mixture is reacted at 60-80℃ for 2-6 hours under nitrogen protection; after the reaction is completed, the mixture is distilled under reduced pressure at 80-100℃ and a vacuum degree of -0.08 to -0.09 MPa for 1-2 hours to obtain aminopropylsilazane.

[0014] The mass ratio of the methyl vinyl polysilazane to γ-aminopropyltriethoxysilane, anhydrous toluene, and dibutyltin dilaurate is 100:3-10:200-500:0.5-1.5.

[0015] The preparation method of the silanized boehmite includes the following steps: boehmite and γ-aminopropyltriethoxysilane are added to anhydrous toluene and heated to react at 80-100°C for 2-4 hours under nitrogen protection. After the reaction is completed, the mixture is centrifuged, washed three times with anhydrous toluene, and dried under vacuum at 80°C for 4-6 hours to obtain silanized boehmite.

[0016] The mass ratio of boehmite to γ-aminopropyltriethoxysilane and anhydrous toluene is 100:3-10:500-1000.

[0017] The preparation method of the hydroxylated boron nitride nanosheets includes the following steps: dispersing hexagonal boron nitride powder in mixed acid and stirring at 60-80℃ for 6-12 hours; centrifuging and washing until the pH of the filtrate is 6-7; dispersing the precipitate in deionized water and ultrasonically exfoliating for 2-4 hours; centrifuging at 3000-5000 rpm for 10-20 minutes; taking the upper suspension and freeze-drying to obtain hydroxylated boron nitride nanosheets.

[0018] The mass ratio of the hexagonal boron nitride powder to the mixed acid is 100:1000-2000, and the mixed acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1; the ultrasonic power of the ultrasonic ablation is 200-400 watts.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This application modifies methylvinyl polysilazane with γ-aminopropyltriethoxysilane, introducing aminopropyl side chains into the polysilazane backbone. These aminopropyl side chains can form hydrogen bonds and coordination bonds with the hydroxyl groups on the natural alumina layer of the positive electrode aluminum foil, significantly improving the interfacial adhesion between the undercoating and the positive electrode aluminum foil. During long-term storage at 60°C, this strong interfacial adhesion effectively inhibits the peeling of the active material layer and electrode curling caused by binder softening, ensuring that the undercoating maintains a stable adhesion state even at high temperatures.

[0020] 2. This application combines silanized boehmite with hydroxylated boron nitride nanosheets. Under the coating shear force, the silanized boehmite aligns parallel to the surface of the positive electrode aluminum foil, forming a dense physical barrier of stacked layers, which acts as a physical barrier against punctures. The hydroxylated boron nitride nanosheets are embedded in the gaps between the boehmite layers, also exhibiting an in-plane orientation. Utilizing their high in-plane thermal conductivity, they construct in-plane thermal bridges, allowing the Joule heat generated at the puncture point to diffuse rapidly along the plane of the aluminum foil, preventing heat accumulation in localized areas. Simultaneously, the boehmite layer has low thermal conductivity in the thickness direction, further blocking heat flow to the diaphragm side, thereby reducing the risk of diaphragm thermal shrinkage.

[0021] 3. This application introduces di-tert-butyl peroxide as a latent initiator into the primer slurry. During the curing stage at 100-110℃, the decomposition rate of di-tert-butyl peroxide is less than 2%, and the vinyl side chains from methyl vinyl polysilazane in aminopropyl silazane are largely preserved. When the battery is subjected to thermal abuse such as needle penetration, and the local temperature rise exceeds 150℃, di-tert-butyl peroxide rapidly decomposes to generate free radicals, initiating thermal polymerization of vinyl groups or dehydrogenation coupling reactions with residual silane-hydrogen bonds, causing aminopropyl silazane to rapidly form a highly cross-linked rigid network. This thermoresponsive cross-linking locks the in-plane oriented silanized boehmite and hydroxylated boron nitride nanosheets into a rigid composite framework, preventing the primer coating from collapsing and losing its barrier function at high temperatures, thus maintaining the structural integrity of the coating.

[0022] 4. The aminopropylsilazane in this application has aminopropyl side chains, the surface of silanized boehmite is grafted with aminopropylsilane, and the surface of hydroxylated boron nitride nanosheets has hydroxyl groups. These surface groups can form hydrogen bonds and other interactions, giving the three components good compatibility and dispersion stability in the primer slurry. The organosilane segments on the surface of silanized boehmite have a similar structure to the main chain of aminopropylsilazane, which improves the compatibility between the filler and the matrix, making the boehmite layer uniformly dispersed in the matrix and maintaining orientation stability. The hydroxyl groups on the surface of hydroxylated boron nitride nanosheets improve their dispersibility in polar solvents, which is beneficial for in-plane orientation. At the same time, the hydroxyl groups form weak interactions with the silicon-hydrogen bonds or nitrogen-hydrogen bonds in aminopropylsilazane, further anchoring the filler position and preventing the filler from debonding from the matrix during high-temperature storage. Attached Figure Description

[0023] Figure 1 A comparison chart showing the test results of the physical properties of the primer-coated positive electrode current collector; in Figure 1 In the figure, A represents a comparison of the peel strength results of the primer positive electrode current collector; in Figure 1 In the figure, B represents a comparison of the in-plane thermal conductivity results of the bottom-coated positive electrode current collector; in Figure 1 The graph shows a comparison of the results of the thickness-direction thermal conductivity of the bottom-coated positive electrode current collector, where C represents the C value. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] In the specific embodiments of this application, the sources of various main raw materials are briefly described as follows: Methyl vinyl polysilazane: purchased from Guangzhou Honghai Chemical Technology Co., Ltd., CAS No. 503590-70-3.

[0026] γ-aminopropyltriethoxysilane: purchased from Nantong Runfeng Petrochemical Co., Ltd., CAS No. 919-30-2, model: silane coupling agent KH-550.

[0027] Anhydrous toluene: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 108-88-3, model: industrial grade anhydrous toluene.

[0028] Dibutyltin dilaurate: purchased from Wuhan Kanos Technology Co., Ltd., CAS No. 77-58-7, model: DY-12.

[0029] Boehmite: Purchased from Xuancheng Jingrui New Materials Co., Ltd., CAS No. 1318-23-6, radial dimension 1μm.

[0030] Hexagonal boron nitride powder: purchased from Liaoning Borda Technology Co., Ltd., CAS No. 10043-11-5, model: h-BN nano powder.

[0031] Concentrated sulfuric acid: purchased from Hubei Zhonglong Kangcheng Fine Chemical Co., Ltd., CAS number 7664-93-9, model: industrial grade concentrated sulfuric acid.

[0032] Concentrated nitric acid: purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS number 7697-37-2, model: industrial grade concentrated nitric acid.

[0033] N-Methylpyrrolidone: Purchased from Shandong Xinheng Chemical Co., Ltd., CAS No. 872-50-4, model: electronic grade NMP.

[0034] Di-tert-butyl peroxide: purchased from Shandong Xinheng Chemical Co., Ltd., CAS No. 110-05-4, model: initiator A, purity 99%.

[0035] Zirconia spheres: Purchased from Pingxiang Jinrui New Materials Co., Ltd., CAS No. 1314-23-4, model: Yttrium stabilized zirconia spheres, diameter 3mm.

[0036] Positive electrode aluminum foil: purchased from Jiangsu Dingsheng New Energy Materials Co., Ltd., model: 12μm battery-grade double-sided bright aluminum foil.

[0037] Lithium nickel cobalt manganese oxide: purchased from Ningbo Ronbay New Energy Technology Co., Ltd., CAS number 346417-97-8, model: NCM811.

[0038] Artificial graphite: purchased from BTR New Materials Group Co., Ltd., CAS No. 7782-42-5.

[0039] Lithium hexafluorophosphate: Purchased from Do-Fluoride New Materials Co., Ltd., CAS No. 21324-40-3, model: battery grade lithium hexafluorophosphate.

[0040] Ethylene carbonate: Purchased from Shandong Haike Xinyuan Material Technology Co., Ltd., CAS No. 96-49-1, model: battery grade ethylene carbonate.

[0041] Ethyl methyl carbonate: purchased from Shandong Haike Xinyuan Material Technology Co., Ltd., CAS number 623-53-0, model: battery grade ethyl methyl carbonate.

[0042] Dimethyl carbonate: Purchased from Shandong Haike Xinyuan Material Technology Co., Ltd., CAS No. 616-38-6, model: battery grade dimethyl carbonate.

[0043] The technical solution of this application is as follows: A high-temperature safety-graded positive electrode current collector includes a positive electrode aluminum foil and a base coating disposed on its surface. The base coating is obtained by coating and curing a base coating slurry, which includes aminopropylsilazane, silanized boehmite, and hydroxylated boron nitride nanosheets. Aminopropylsilazane is prepared by the condensation reaction of methylvinylpolysilazane and γ-aminopropyltriethoxysilane; In lithium-ion battery manufacturing, the surface of the positive electrode aluminum foil needs to be coated with a base layer to support the active material. Existing technologies mostly use polyvinylidene fluoride (PVDF) as a binder. However, PVDF has a low glass transition temperature, and the binder softens during long-term high-temperature storage, causing the base layer to debond from the interface of the positive electrode aluminum foil, resulting in the peeling off of the active material layer.

[0044] To overcome this deficiency, we used aminopropylsilazane as the base resin for the primer coating. This aminopropylsilazane was prepared by the condensation reaction of methylvinyl polysilazane and γ-aminopropyltriethoxysilane in anhydrous toluene via a dibutyltin dilaurate catalytic reaction. The main chain consists of silicon-nitrogen-silicon bonds, with aminopropyl groups introduced into the side chains. The amino groups in the aminopropyl side chains can form hydrogen bonds with the hydroxyl groups on the natural alumina layer of the positive electrode aluminum foil, while simultaneously forming coordinate bonds between nitrogen and aluminum atoms. These two forces significantly improve the interfacial bonding strength between the primer coating and the positive electrode aluminum foil. During the curing process, the dibutyltin dilaurate remaining from the preparation of aminopropylsilazane continues to play a catalytic role. When the coating is exposed to air, some of the Si-H and Si-NH groups on the methylvinylsilazane backbone undergo hydrolysis and condensation with ambient moisture under the action of the residual catalyst, generating an initial Si-O-Si crosslinked network. However, the crosslinking density is controlled at 40%-70%, and sufficient thermally responsive vinyl and Si-H groups are retained in the system for further reaction at temperatures above 150°C. Thus, during storage at both room temperature and high temperatures, the base coating maintains a flexible polymer state, with strong interfacial bonding, inhibiting the peeling of the active material layer.

[0045] Silanized boehmite is prepared by reacting boehmite with γ-aminopropyltriethoxysilane; Simply improving interfacial adhesion is insufficient to address mechanical abuse such as needle punching. While boehmite in existing technologies can provide some barrier properties, unmodified boehmite exhibits poor compatibility with the organic matrix, resulting in uneven dispersion in the slurry and difficulty in forming a regular oriented arrangement during coating. Therefore, this application silanizes boehmite by reacting it with γ-aminopropyltriethoxysilane in anhydrous toluene, grafting aminopropylsilane onto the boehmite surface. The organosilane segments on the silanized boehmite surface have a similar structure and polarity match to the aminopropylsilazane backbone, improving their compatibility and ensuring uniform dispersion of the boehmite layer within the matrix. During slot coating, the shear force generated in the coating gap causes the silanized boehmite to align parallel to the surface of the positive electrode aluminum foil, forming a dense physical barrier of stacked layers. This effectively prevents penetrating material from reaching the surface of the positive electrode aluminum foil, preventing direct contact between the positive and negative electrodes and thus avoiding internal short circuits.

[0046] Hydroxylated boron nitride nanosheets are prepared by hydroxylation of hexagonal boron nitride powder.

[0047] However, needle penetration, in addition to physical penetration, also generates localized Joule heating. Existing boehmite has poor thermal conductivity, resulting in low overall thermal conductivity of the coating. Heat can only be conducted to the diaphragm along the thickness direction, causing the local temperature of the diaphragm to exceed the thermal shrinkage temperature. To address this problem, this application introduces hydroxylated boron nitride nanosheets into the primer slurry. These hydroxylated boron nitride nanosheets are prepared by ultrasonic exfoliation after hydroxylation treatment with mixed acid from hexagonal boron nitride powder. The hydroxyl groups on the surface improve dispersibility in polar solvents and prevent agglomeration and sedimentation. Under the coating shear force, the hydroxylated boron nitride nanosheets embed into the gaps between the silanized boehmite layers, oriented parallel to the surface of the positive electrode aluminum foil, forming an intercalation structure with the boehmite layers. Boron nitride nanosheets exhibit anisotropic characteristics of high in-plane thermal conductivity and low thermal conductivity in the thickness direction. They form in-plane thermal bridges between boehmite layers, allowing the Joule heat generated at the puncture point to diffuse rapidly along the plane of the positive electrode aluminum foil. The heat is dispersed in-plane to areas far from the puncture point, preventing concentrated conduction to the diaphragm side. Simultaneously, the silanized boehmite layer itself has low thermal conductivity in the thickness direction, further blocking heat transfer to the diaphragm and reducing the risk of diaphragm thermal shrinkage.

[0048] The preparation method of the primer slurry includes the following steps: Dissolve 100 parts by weight of aminopropylsilazane in N-methylpyrrolidone to prepare an N-methylpyrrolidone solution of aminopropylsilazane with a solid content of 25-35%. 150-300 parts by weight of silanized boehmite and 50-150 parts by weight of hydroxylated boron nitride nanosheets were added to N-methylpyrrolidone and ball-milled to obtain a pre-dispersed slurry; The pre-dispersed slurry is added to an N-methylpyrrolidone solution of aminopropylsilazane, and 0.5-1.5 parts by weight of di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone is added. N-methylpyrrolidone is then added to adjust the total solid content to 15-25%. The mixture is stirred at low speed for 30 minutes to obtain the primer slurry.

[0049] Nevertheless, if the local temperature rise continues to increase, the primer coating still faces the risk of structural collapse. Existing polysilazane ceramic transformation temperatures are typically high, making it impossible to quickly form a rigid framework within the local temperature rise range caused by needle penetration. Therefore, this application incorporates di-tert-butyl peroxide into the primer slurry. During the curing stage, di-tert-butyl peroxide remains largely undecomposed, allowing the vinyl side chains from methyl vinyl polysilazane in aminopropyl silazane to be fully preserved. If the local temperature rise exceeds 150°C, di-tert-butyl peroxide rapidly decomposes to generate free radicals, initiating thermal polymerization of the vinyl groups or dehydrogenation coupling with residual silane-hydrogen bonds, rapidly forming a highly cross-linked rigid network. This network locks the in-plane oriented silanized boehmite and hydroxylated boron nitride nanosheets into a rigid composite framework, preventing the primer coating from collapsing and losing its barrier function at high temperatures. When the temperature continues to rise above 400℃, the aforementioned highly cross-linked polysilazane network further breaks down and rearranges, reacting with endogenous oxygen sources such as residual silicon-oxygen bonds and hydroxyl condensation water on the filler surface in the system, and gradually transforms into an amorphous silicon-carbon-nitrogen-oxygen ceramic phase, forming a ceramic-lamellae interlocking structure with the oriented filler network, maintaining structural integrity under extreme high temperatures.

[0050] The specific parameters of the ball mill are as follows: the ball milling medium is zirconia balls, the ball-to-material mass ratio is (3-5):1, the ball milling speed is 200-400 revolutions per minute, and the ball milling time is 2-3 hours.

[0051] The coating and curing process specifically includes the following steps: applying a primer slurry to the surface of the corona-roughened positive electrode aluminum foil using a slot coating method, with a wet film thickness of 10-15 micrometers, a coating speed of 10-20 meters per minute, and a coating gap of 1.2-1.5 times the aforementioned wet film thickness; then pre-drying at 80°C for 20 minutes, followed by curing in an oven at 100-110°C for 60 minutes, with the curing atmosphere being air and a relative humidity of 40-60%, resulting in a primer coating with a dry thickness of 1.5-3 micrometers.

[0052] The preparation method of the aminopropylsilazane includes the following steps: methyl vinyl polysilazane and γ-aminopropyltriethoxysilane are added to anhydrous toluene, dibutyltin dilaurate is added, and the mixture is reacted at 60-80℃ for 2-6 hours under nitrogen protection; after the reaction is completed, the mixture is distilled under reduced pressure at 80-100℃ and a vacuum degree of -0.08 to -0.09 MPa for 1-2 hours to obtain aminopropylsilazane.

[0053] The mass ratio of the methyl vinyl polysilazane to γ-aminopropyltriethoxysilane, anhydrous toluene, and dibutyltin dilaurate is 100:3-10:200-500:0.5-1.5.

[0054] The preparation method of the silanized boehmite includes the following steps: boehmite and γ-aminopropyltriethoxysilane are added to anhydrous toluene and heated to react at 80-100°C for 2-4 hours under nitrogen protection. After the reaction is completed, the mixture is centrifuged, washed three times with anhydrous toluene, and dried under vacuum at 80°C for 4-6 hours to obtain silanized boehmite.

[0055] The mass ratio of boehmite to γ-aminopropyltriethoxysilane and anhydrous toluene is 100:3-10:500-1000. In this ratio, the amount of γ-aminopropyltriethoxysilane used is higher than the theoretical requirement for conventional monolayer coating. The purpose is to form a high-graft-density aminopropylsilane layer on the boehmite surface, thereby enabling the formation of a continuous hydrogen-bonded network between the filler and the matrix when mixed with aminopropylsilazane, improving interfacial compatibility and dispersion stability, rather than simply achieving physical monolayer coating.

[0056] The preparation method of the hydroxylated boron nitride nanosheets includes the following steps: dispersing hexagonal boron nitride powder in mixed acid and stirring at 60-80℃ for 6-12 hours; centrifuging and washing until the pH of the filtrate is 6-7; dispersing the precipitate in deionized water and ultrasonically exfoliating for 2-4 hours; centrifuging at 3000-5000 rpm for 10-20 minutes; taking the upper suspension and freeze-drying to obtain hydroxylated boron nitride nanosheets.

[0057] The mass ratio of the hexagonal boron nitride powder to the mixed acid is 100:1000-2000, and the mixed acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1; the ultrasonic power of the ultrasonic ablation is 200-400 watts.

[0058] In existing technologies, simple blending of fillers lacks interfacial matching with the matrix, leading to filler debonding during high-temperature storage and resulting in coating performance degradation. This application solves this problem through surface group matching design. Aminopropylsilazane has aminopropyl side chains, silanized boehmite is grafted with aminopropylsilane, and hydroxylated boron nitride nanosheets have hydroxyl groups on their surface. These surface groups can form hydrogen bonds and other interactions, creating a continuous, strong interfacial bonding network throughout the coating. The organosilane segments on the surface of silanized boehmite have good compatibility with the aminopropylsilazane matrix, ensuring uniform dispersion and stable orientation of the boehmite layer. The hydroxyl groups on the surface of the hydroxylated boron nitride nanosheets form weak interactions with the silicon-hydrogen bonds or nitrogen-hydrogen bonds in the aminopropylsilazane, further anchoring the filler position and preventing filler debonding during high-temperature storage.

[0059] To achieve the aforementioned microstructure, a slotted coating method was employed in the coating and curing process. This method utilizes the shear force generated by the coating gaps to simultaneously orient the silanized boehmite and hydroxylated boron nitride nanosheets in-plane. After pre-drying to remove most of the solvent, the nanosheets were transferred to a lower-temperature oven for curing in an air atmosphere with relative humidity controlled within a specific range. Under these conditions, the dibutyltin dilaurate remaining from the preparation of aminopropylsilazane continued to catalyze the hydrolysis and condensation of silicon-hydrogen bonds and silicon-nitrogen bonds. Some of the silicon-hydrogen bonds in the aminopropylsilazane reacted with ambient moisture to form an initial Si-O-Si network, and the aminopropyl side chains bonded to the surface of the positive electrode aluminum foil. This process ensured both the coating strength and interfacial adhesion while preserving the activity of vinyl groups and silicon-hydrogen bonds, providing a foundation for subsequent thermally responsive crosslinking.

[0060] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products.

[0061] Example 1 Preparation of aminopropylsilazane. 100 parts by weight of methylvinyl polysilazane and 10 parts by weight of γ-aminopropyltriethoxysilane were added to 350 parts by weight of anhydrous toluene, along with 0.5 parts by weight of dibutyltin dilaurate. The reaction was carried out at 80°C for 4 hours under nitrogen protection. After the reaction was completed, the mixture was distilled under reduced pressure at 90°C and a vacuum of -0.09 MPa for 2 hours to obtain aminopropylsilazane.

[0062] Preparation of silanized boehmite. 100 parts by mass of boehmite and 3 parts by mass of γ-aminopropyltriethoxysilane were added to 500 parts by mass of anhydrous toluene and reacted at 100°C for 3 hours under nitrogen protection. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous toluene, and dried under vacuum at 80°C for 4 hours to obtain silanized boehmite.

[0063] Preparation of hydroxylated boron nitride nanosheets. 100 parts by weight of hexagonal boron nitride powder were dispersed in 2000 parts by weight of a mixed acid, which was a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1. The mixture was stirred at 70°C for 6 hours. After centrifugation and washing until the pH of the filtrate reached 7.0, the precipitate was dispersed in deionized water and ultrasonically exfoliated for 4 hours at a power of 400 W. Subsequently, the mixture was centrifuged at 4000 r / min for 10 minutes. The supernatant was collected and freeze-dried to obtain hydroxylated boron nitride nanosheets.

[0064] Preparation of the primer slurry: 100 parts by mass of aminopropylsilazane were dissolved in N-methylpyrrolidone to prepare an aminopropylsilazane-N-methylpyrrolidone solution with a solid content of 25%. 225 parts by mass of silanized boehmite and 50 parts by mass of hydroxylated boron nitride nanosheets were added to the N-methylpyrrolidone solution and ball-milled to obtain a pre-dispersed slurry. The ball milling media was zirconia balls, with a ball-to-material mass ratio of 4:1. The ball milling speed was 200 r / min, and the milling time was 3 hours. The pre-dispersed slurry was added to the aminopropylsilazane-N-methylpyrrolidone solution, along with 1.0 part by mass of di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone. N-methylpyrrolidone was then added to adjust the total solid content to 15%. The mixture was stirred at low speed for 30 minutes to obtain the primer slurry.

[0065] Coating and curing. The primer slurry was applied to the corona-roughened aluminum foil surface using a slot coating method, with a wet film thickness of 15 μm, a coating speed of 15 m / min, and a coating gap of 1.2 times the aforementioned wet film thickness. After pre-drying at 80°C for 20 minutes, it was then cured in a 110°C oven for 60 minutes in an air atmosphere with a relative humidity of 50%, resulting in a primer-coated positive current collector with a dry coating thickness of approximately 3 μm.

[0066] Example 2 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Preparation of aminopropylsilazane. 100 parts by weight of methylvinyl polysilazane and 8 parts by weight of γ-aminopropyltriethoxysilane were added to 500 parts by weight of anhydrous toluene, and 1.0 part by weight of dibutyltin dilaurate was added. The mixture was reacted at 60°C for 6 hours under nitrogen protection. After the reaction was completed, the mixture was distilled under reduced pressure at 100°C and a vacuum of -0.08 MPa for 1 hour to obtain aminopropylsilazane.

[0067] Preparation of silanized boehmite. 100 parts by mass of boehmite and 8 parts by mass of γ-aminopropyltriethoxysilane were added to 1000 parts by mass of anhydrous toluene and reacted at 80°C for 4 hours under nitrogen protection. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous toluene, and dried under vacuum at 80°C for 5 hours to obtain silanized boehmite.

[0068] Preparation of hydroxylated boron nitride nanosheets. 100 parts by weight of hexagonal boron nitride powder were dispersed in 1000 parts by weight of a mixed acid, which was a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1. The mixture was stirred at 80°C for 12 hours. After centrifugation and washing until the pH of the filtrate reached 6.0, the precipitate was dispersed in deionized water and ultrasonically exfoliated for 2 hours at a power of 200 W. Subsequently, the mixture was centrifuged at 5000 r / min for 15 minutes. The supernatant was collected and freeze-dried to obtain hydroxylated boron nitride nanosheets.

[0069] Preparation of the primer slurry: 100 parts by mass of aminopropylsilazane were dissolved in N-methylpyrrolidone to prepare an aminopropylsilazane-N-methylpyrrolidone solution with a solid content of 35%. 300 parts by mass of silanized boehmite and 100 parts by mass of hydroxylated boron nitride nanosheets were added to the N-methylpyrrolidone solution and ball-milled to obtain a pre-dispersed slurry. The ball milling media was zirconia balls, with a ball-to-material mass ratio of 5:1. The ball milling speed was 300 r / min, and the milling time was 2 hours. The pre-dispersed slurry was added to the aminopropylsilazane-N-methylpyrrolidone solution, along with 1.5 parts by mass of di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone. N-methylpyrrolidone was then added to adjust the total solid content to 20%. The mixture was stirred at low speed for 30 minutes to obtain the primer slurry.

[0070] Coating and curing. The primer slurry was applied to the corona-roughened aluminum foil surface using a slot coating method, with a wet film thickness of 10 μm, a coating speed of 20 m / min, and a coating gap of 1.35 times the aforementioned wet film thickness. After pre-drying at 80°C for 20 minutes, it was then cured in a 100°C oven for 60 minutes in an air atmosphere with a relative humidity of 60%, resulting in a primer-coated positive current collector with a dry coating thickness of approximately 1.5 μm.

[0071] Example 3 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Preparation of aminopropylsilazane. 100 parts by weight of methylvinyl polysilazane and 3 parts by weight of γ-aminopropyltriethoxysilane were added to 200 parts by weight of anhydrous toluene, and 1.5 parts by weight of dibutyltin dilaurate were added. The reaction was carried out at 70°C for 2 hours under nitrogen protection. After the reaction was completed, the mixture was distilled under reduced pressure at 80°C and a vacuum of -0.09 MPa for 1.5 hours to obtain aminopropylsilazane.

[0072] Preparation of silanized boehmite. 100 parts by mass of boehmite and 10 parts by mass of γ-aminopropyltriethoxysilane were added to 500 parts by mass of anhydrous toluene and reacted at 90°C for 2 hours under nitrogen protection. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous toluene, and dried under vacuum at 80°C for 6 hours to obtain silanized boehmite.

[0073] Preparation of hydroxylated boron nitride nanosheets. 100 parts by weight of hexagonal boron nitride powder were dispersed in 1500 parts by weight of a mixed acid, which was a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1. The mixture was stirred at 60°C for 9 hours. After centrifugation and washing until the pH of the filtrate reached 6.5, the precipitate was dispersed in deionized water and ultrasonically exfoliated for 3 hours at a power of 300 W. Subsequently, the mixture was centrifuged at 3000 r / min for 20 minutes. The supernatant was collected and freeze-dried to obtain hydroxylated boron nitride nanosheets.

[0074] Preparation of the primer slurry: 100 parts by mass of aminopropylsilazane were dissolved in N-methylpyrrolidone to prepare an N-methylpyrrolidone solution with an aminopropylsilazane solid content of 30%. 150 parts by mass of silanized boehmite and 150 parts by mass of hydroxylated boron nitride nanosheets were added to the N-methylpyrrolidone solution and ball-milled to obtain a pre-dispersed slurry. The ball milling media was zirconia balls, with a ball-to-material mass ratio of 3:1. The ball milling speed was 400 r / min, and the milling time was 2.5 hours. The pre-dispersed slurry was added to the N-methylpyrrolidone solution of aminopropylsilazane, along with 0.5 parts by mass of di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone. N-methylpyrrolidone was then added to adjust the total solid content to 25%. The mixture was stirred at low speed for 30 minutes to obtain the primer slurry.

[0075] Coating and curing. The primer slurry was applied to the corona-roughened aluminum foil surface using a slot coating method, with a wet film thickness of 12.5 μm, a coating speed of 10 m / min, and a coating gap of 1.5 times the aforementioned wet film thickness. After pre-drying at 80°C for 20 minutes, it was then cured in a 105°C oven for 60 minutes in an air atmosphere with a relative humidity of 40%, resulting in a primer-coated positive current collector with a dry coating thickness of approximately 2.5 μm.

[0076] Example 4 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Preparation of aminopropylsilazane. 100 parts by weight of methylvinyl polysilazane and 8 parts by weight of γ-aminopropyltriethoxysilane were added to 350 parts by weight of anhydrous toluene, and 1.0 part by weight of dibutyltin dilaurate was added. The reaction was carried out at 70°C for 4 hours under nitrogen protection. After the reaction was completed, the mixture was distilled under reduced pressure at 90°C and a vacuum of -0.085 MPa for 1.5 hours to obtain aminopropylsilazane.

[0077] Preparation of silanized boehmite. 100 parts by mass of boehmite and 8 parts by mass of γ-aminopropyltriethoxysilane were added to 750 parts by mass of anhydrous toluene and reacted at 90°C for 3 hours under nitrogen protection. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous toluene, and dried under vacuum at 80°C for 5 hours to obtain silanized boehmite.

[0078] Preparation of hydroxylated boron nitride nanosheets. 100 parts by weight of hexagonal boron nitride powder were dispersed in 1500 parts by weight of a mixed acid, which was a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1. The mixture was stirred at 70°C for 9 hours. After centrifugation and washing until the pH of the filtrate reached 6.5, the precipitate was dispersed in deionized water and ultrasonically exfoliated for 3 hours at a power of 300 W. Subsequently, the mixture was centrifuged at 4000 r / min for 15 minutes. The supernatant was collected and freeze-dried to obtain hydroxylated boron nitride nanosheets.

[0079] Preparation of the primer slurry. 100 parts by mass of aminopropylsilazane were dissolved in N-methylpyrrolidone to prepare an aminopropylsilazane-N-methylpyrrolidone solution with a solid content of 30%. 225 parts by mass of silanized boehmite and 100 parts by mass of hydroxylated boron nitride nanosheets were added to the N-methylpyrrolidone solution. The mixture was ball-milled to obtain a pre-dispersed slurry. Zirconia balls were used as the milling medium, with a ball-to-material mass ratio of 4:1. The milling speed was 300 r / min, and the milling time was 2.5 hours. The pre-dispersed slurry was added to the aminopropylsilazane-N-methylpyrrolidone solution, along with 1.0 part by mass of di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone. N-methylpyrrolidone was then added to adjust the total solid content to 20%. The mixture was stirred at low speed for 30 minutes to obtain the primer slurry.

[0080] Coating and curing. The primer slurry was applied to the corona-roughened aluminum foil surface using a slot coating method, with a wet film thickness of 12.5 μm, a coating speed of 15 m / min, and a coating gap 1.35 times the aforementioned wet film thickness. After pre-drying at 80°C for 20 minutes, it was then cured in a 105°C oven for 60 minutes in an air atmosphere with a relative humidity of 50%, resulting in a primer-coated positive current collector with a dry coating thickness of approximately 2 μm.

[0081] Comparative Example 1 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: In the preparation of aminopropylsilazane, γ-aminopropyltriethoxysilane is not used; instead, methyl vinyl polysilazane is used directly as a binder.

[0082] Comparative Example 2 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: In the preparation of silanized boehmite, γ-aminopropyltriethoxysilane is not used to modify boehmite; unmodified boehmite is used directly.

[0083] Comparative Example 3 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: In the preparation of hydroxylated boron nitride nanosheets, no mixed acid hydroxylation treatment or ultrasonic exfoliation is performed; unmodified hexagonal boron nitride powder is used directly.

[0084] Comparative Example 4 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: No di-tert-butyl peroxide is added during the preparation of the primer slurry.

[0085] Comparative Example 5 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: In the coating and curing process, a scraping method is used instead of slot coating, and the coating gap is not used to control the shear force.

[0086] Comparative Example 6 In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: In the coating and curing step, the curing temperature is increased to 120℃ and the curing time is extended to 90 minutes.

[0087] Performance Test Results and Analysis The bottom-coated positive electrode current collectors prepared in Examples 1 to 4 and Comparative Examples 1 to 6 were assembled into pouch cells with positive electrode active material layers. The positive electrode active material was lithium nickel cobalt manganese oxide, the negative electrode was artificial graphite, and the electrolyte was a mixture of 1 mol / L lithium hexafluorophosphate dissolved in ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. The assembled cells were subjected to the following tests: After storage at 60°C for 7 days, the 180° peel strength between the bottom coating and the positive electrode aluminum foil was tested according to GB / T 2792. The in-plane thermal conductivity and thickness-direction thermal conductivity of the bottom coating were tested using the laser scintillation method. A needle penetration test was performed according to GB / T 31485, with a 3 mm diameter steel needle penetrating the center of the cell at a speed of 80 mm / s. The highest temperature at the penetration point and whether ignition or explosion occurred were recorded. Simultaneously, the gas production and capacity retention after 7 days of storage at 60°C were recorded. The specific test results are shown in Table 1 and... Figure 1 As shown.

[0088] Interface combined with performance, specifically as follows Figure 1 As shown, the peel strengths of Examples 1 to 4 are 15.0 N / m, 14.0 N / m, 16.0 N / m, and 17.0 N / m, respectively. See details... Figure 1 The A values ​​in all examples are higher than those in the comparative example. In Examples 1 to 4, the aminopropyl side chain of aminopropylsilazane forms hydrogen bonds and coordination bonds with the hydroxyl groups on the natural alumina layer of the positive electrode aluminum foil surface. This chemical bonding significantly improves the interfacial adhesion.

[0089] Comparative Example 1, without aminopropyl modification, exhibits only physical adsorption such as van der Waals forces between the methyl vinyl polysilazane and the positive electrode aluminum foil, resulting in weak interfacial adhesion and a peel strength of only 6.0 N / m. Comparative Example 2, using unmodified boehmite, suffers from poor compatibility between the filler and the aminopropyl polysilazane, leading to agglomeration and phase separation in the slurry. Defects exist within the coating after application, and stress concentration causes interfacial debonding, reducing the peel strength to 10.0 N / m. Comparative Example 6, due to excessively high curing temperature, experiences over-crosslinking of the polysilazane, increasing coating brittleness and decreasing interfacial stress matching with the positive electrode aluminum foil, resulting in a peel strength of 8.0 N / m.

[0090] From the perspective of thermal conductivity, such as Figure 1As shown in B, the in-plane thermal conductivity of Examples 1 to 4 are 3.5 W / (m·K), 3.0 W / (m·K), 4.0 W / (m·K), and 4.2 W / (m·K), respectively, all higher than that of the comparative example. Figure 1 As shown in C, the thermal conductivity in the thickness direction is 0.60 W / (m·K), 0.70 W / (m·K), 0.50 W / (m·K), and 0.45 W / (m·K), respectively, all lower than that of the comparative example, demonstrating the anisotropic thermal conductivity characteristics of the in-plane oriented intercalation structure. In Examples 1 to 4, silanized boehmite and hydroxylated boron nitride nanosheets are oriented parallel to the surface of the positive electrode aluminum foil under the action of slit coating shear force. The hydroxylated boron nitride nanosheets are embedded in the gaps between the silanized boehmite layers to form an intercalation structure, building a continuous in-plane thermal conductivity channel.

[0091] Comparative Example 3 used unmodified hexagonal boron nitride powder. The particles agglomerated and settled in the slurry, failing to embed into the gaps between the boehmite layers to form continuous thermal conductive channels. Its in-plane thermal conductivity was only 1.2 W / (m·K). Comparative Example 5 used a blade coating method, which lacked the shear force generated by slot coating. The silanized boehmite and hydroxylated boron nitride nanosheets were randomly distributed and could not form an in-plane oriented arrangement. Its in-plane thermal conductivity was only 1.8 W / (m·K), while the thermal conductivity in the thickness direction was as high as 1.20 W / (m·K), resulting in poor thermal insulation performance.

[0092] In Comparative Example 2, the unmodified boehmite was unevenly dispersed, disrupting the regularity of the intercalation structure, resulting in an in-plane thermal conductivity of only 1.5 W / (m·K). Regarding the thermal conductivity in the thickness direction, Examples 1 to 4 all had values ​​below 0.70 W / (m·K), indicating that heat conduction towards the diaphragm was effectively suppressed. However, Comparative Example 5, due to the lack of filler orientation, exhibited a thickness-direction thermal conductivity as high as 1.20 W / (m·K), indicating poor thermal insulation performance.

[0093] Table 1. Test results of safety and electrochemical performance of the primer-coated positive electrode current collector Example 1 85 Passed, no fire or explosion. 1.2 96 Example 2 90 Passed, no fire or explosion. 1.5 95 Example 3 80 Passed, no fire or explosion. 1.0 97 Example 4 75 Passed, no fire or explosion. 0.8 98 Comparative Example 1 160 Failed, fire broke out 4.5 82 Comparative Example 2 140 Failed, fire broke out 3.0 88 Comparative Example 3 150 Failed, fire broke out 2.5 89 Comparative Example 4 170 Failed, fire broke out 2.2 91 Comparative Example 5 155 Failed, fire broke out 2.0 92 Comparative Example 6 165 Failed, fire broke out 3.8 85 Table 1 shows the test results of the safety and electrochemical performance of the primer-coated positive electrode current collector. From the perspective of needle penetration safety performance, the highest needle penetration temperatures of Examples 1 to 4 were 85℃, 90℃, 80℃, and 75℃, respectively, all lower than the comparative examples, and no fire or explosion occurred. This is attributed to the rapid lateral dispersion of heat by the in-plane oriented thermally conductive network and the thermally responsive crosslinking locking the structure at high temperatures. Comparative Example 4 did not contain di-tert-butyl peroxide; during needle penetration, the aminopropylsilazane could not rapidly crosslink to form a rigid framework, causing the coating to collapse at high temperatures and lose its barrier function, resulting in a sharp increase in its needle penetration temperature to 170℃. In Comparative Example 6, the di-tert-butyl peroxide decomposed prematurely during the 120℃ curing stage, and a large amount of vinyl groups were consumed during curing, resulting in insufficient residual crosslinkable groups during needle penetration and poor thermal locking effect; as shown in Table 1, its temperature increased to 165℃. Due to weak interfacial bonding, the coating in Comparative Example 1 easily peeled off from the surface of the positive electrode aluminum foil during needle penetration, losing its physical barrier; as shown in Table 1, its temperature increased to 160℃. In Comparative Example 5, the heat could not be dispersed laterally due to the lack of orientation of the filler, resulting in localized accumulation and a temperature increase to 155°C. Comparative Examples 2 and 3 also experienced needle penetration temperatures of 140°C and 150°C, respectively, due to their respective structural defects, and both ignited.

[0094] Regarding high-temperature storage performance, as shown in Table 1, the gas production rates of Examples 1 to 4 were 1.2 mL, 1.5 mL, 1.0 mL, and 0.8 mL, respectively, all lower than the comparative example. Their capacity retention rates were 96%, 95%, 97%, and 98%, respectively, all higher than the comparative example. This is because the strong interfacial bonding network inhibited the peeling of the active material layer at high temperatures, reducing side reactions caused by interfacial failure. Comparative Example 1, due to poor interfacial bonding, experienced active material layer peeling during high-temperature storage, resulting in increased contact area between the exposed interface and the electrolyte, leading to an increase in gas production to 4.5 mL and a decrease in capacity retention rate to 82%. Comparative Example 4, although not affecting the room-temperature interface, suffered from insufficient structural locking at high temperatures. During long-term storage, stress release within the coating led to microcracks, exacerbating electrolyte penetration, and as shown in Table 1, its gas production increased to 2.2 mL. Comparative Example 6, due to over-curing, exhibited high coating brittleness, resulting in microcrack propagation during long-term storage, and as shown in Table 1, its gas production reached as high as 3.8 mL, with a decrease in capacity retention rate to 85%. Comparative Examples 2 and 3 also suffered from coating structure defects due to filler dispersion and orientation issues. As shown in Table 1, their gas production was 3.0 mL and 2.5 mL, respectively, and their capacity retention was 88% and 89%, respectively.

[0095] Test results show that this application achieves a balance between rapid in-plane heat dissipation and high-temperature structural locking by matching the surface groups of aminopropylsilazane, silanized boehmite and hydroxylated boron nitride nanosheets and designing in-plane orientation intercalation, enabling the bottom-coated positive electrode current collector to have excellent interfacial bonding while possessing excellent in-plane bonding strength.

[0096] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-temperature safety-grade bottom-coated positive electrode current collector, characterized in that, The base-coated positive current collector includes a positive aluminum foil and a base coating disposed on its surface. The base coating is obtained by coating and curing a base coating slurry. The base coating slurry includes, by weight, 100 parts of aminopropylsilazane, 150-300 parts of silanized boehmite, 50-150 parts of hydroxylated boron nitride nanosheets, and 0.5-1.0 parts of di-tert-butyl peroxide. Aminopropylsilazane is prepared by the condensation reaction of methyl vinyl polysilazane and γ-aminopropyltriethoxysilane. The preparation method of aminopropylsilazane includes the following steps: adding methyl vinyl polysilazane and γ-aminopropyltriethoxysilane to anhydrous toluene, adding dibutyltin dilaurate, and reacting at 60-80℃ for 2-6 hours under nitrogen protection; after the reaction is completed, distilling under reduced pressure at 80-100℃ and a vacuum degree of -0.08 to -0.09 MPa for 1-2 hours to obtain aminopropylsilazane. Silanized boehmite is prepared by reacting boehmite with γ-aminopropyltriethoxysilane. The preparation method of silanized boehmite includes the following steps: adding boehmite and γ-aminopropyltriethoxysilane into anhydrous toluene, heating and reacting at 80-100°C for 2-4 hours under nitrogen protection; after the reaction is completed, centrifuging, washing three times with anhydrous toluene, and drying under vacuum at 80°C for 4-6 hours to obtain silanized boehmite. Hydroxylated boron nitride nanosheets were prepared by hydroxylation of hexagonal boron nitride powder. The coating curing process includes: pre-drying at 80°C for 20 minutes, followed by curing in an oven at 105°C for 60 minutes.

2. The high-temperature safety bottom-coated positive current collector according to claim 1, characterized in that, The preparation method of the primer slurry includes the following steps: Dissolve aminopropylsilazane in N-methylpyrrolidone to prepare an N-methylpyrrolidone solution with a solid content of 30% aminopropylsilazane. Silanized boehmite and hydroxylated boron nitride nanosheets were added to N-methylpyrrolidone and ball-milled to obtain a pre-dispersed slurry. The pre-dispersed slurry was added to an N-methylpyrrolidone solution of aminopropylsilazane, and di-tert-butyl peroxide pre-dissolved in N-methylpyrrolidone was added. N-methylpyrrolidone was then added to adjust the total solid content to 15-25%. The mixture was stirred at low speed for 30 minutes to obtain the primer slurry.

3. The high-temperature safety bottom-coated positive current collector according to claim 2, characterized in that, The specific parameters of the ball mill are as follows: the ball milling medium is zirconia balls, the ball-to-material mass ratio is (3-5):1, the ball milling speed is 200-400 revolutions per minute, and the ball milling time is 2-3 hours.

4. The high-temperature safety bottom-coated positive current collector according to claim 1, characterized in that, The coating and curing process specifically includes the following steps: The primer slurry is applied to the corona-roughened aluminum foil surface using a slot coating method. The wet film thickness is 10-15 micrometers, the coating speed is 10-20 meters per minute, and the coating gap is 1.2-1.5 times the aforementioned wet film thickness. The curing atmosphere is air with a relative humidity of 40-60%, resulting in a dry primer coating with a thickness of 1.5-3 micrometers.

5. A high-temperature safety-grade bottom-coated positive current collector according to claim 1, characterized in that, The mass ratio of the methyl vinyl polysilazane to γ-aminopropyltriethoxysilane, anhydrous toluene, and dibutyltin dilaurate is 100:3-10:200-500:0.5-1.

5.

6. The high-temperature safety bottom-coated positive current collector according to claim 1, characterized in that, The mass ratio of boehmite to γ-aminopropyltriethoxysilane and anhydrous toluene is 100:3-10:500-1000.

7. A high-temperature safety-grade bottom-coated positive current collector according to claim 1, characterized in that, The preparation method of the hydroxylated boron nitride nanosheets includes the following steps: dispersing hexagonal boron nitride powder in mixed acid and stirring at 60-80℃ for 6-12 hours; centrifuging and washing until the pH of the filtrate is 6-7; dispersing the precipitate in deionized water and ultrasonically exfoliating for 2-4 hours; centrifuging at 3000-5000 rpm for 10-20 minutes; taking the upper suspension and freeze-drying to obtain hydroxylated boron nitride nanosheets.

8. A high-temperature safety-grade bottom-coated positive current collector according to claim 7, characterized in that, The mass ratio of the hexagonal boron nitride powder to the mixed acid is 100:1000-2000, and the mixed acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1; the ultrasonic power of the ultrasonic ablation is 200-400 watts.

Citation Information

Patent Citations

  • Method for coating inorganic particles on lithium secondary battery substrate, and lithium secondary battery including substrate coated by the method

    CN104054195A

  • High-barrier high-heat-resistance polyester material as well as preparation method and application thereof

    CN121293484A

  • Positive electrodes, preparation methods thereof, and rechargeable lithium batteries

    US20260005339A1